Parapagus dicephalus conjoined twins and evaluation of ischiopagus tetrapus conjoined twins in Indonesia: a case report - ., ROCHADI (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2013)
Conjoined twins are rare occurrences in medical practice. In this study, two cases of conjoinedtwins, parapagus dicephalus and ischiopagus tetrapus are reported in Dr. Sardjito General Hospital,Yogyakarta, Indonesia. The first case i.e. five-day-old male parapagus dicephalus conjoinedtwins referred to the hospital. The twins have two heads, two arms and two legs. X-ray examinationreveals two vertebrae collumn, single heart, and single pelvis. Moreover ultrasonographyexamination reveals conjoining of liver and echocardiography examinatin reveals single atrium.The twins were diagnosed as parapagus dicephalus. As a result of their fusion, operative carehad been considered to be unacceptable. After several weeks in neonatal intensive care, theydied. The second case i.e. two-day-old female conjoined twins with conjoining at ischium regionreferred to the hospital. Ultrasonography and abdominal examination reveal conjoining atintestinum, buttock and ischium. The twins was diagnsed as ischiopagus tetrapus. They weresuccessfully separated at 6 months of age. They are alive and well so far for more than 7 years.In conclusion, the prognosis of conjoined twins is related to the type, extent of union and organabnormalities. The successful separation of conjoined twins might be determined by good planningand staff enthusiasm and dedication.